Implementasi IoT pada Sistem Parkir Pintar Berbasis ESP32 dengan Monitoring Real-Time ThingSpeak - Yosafat Exel Osdela Gutomo; Lukman Aditya; Nurhabibah Naibaho (Teknik Elektro Universtias Krisnadwipayana, 2026)
The rapid advancement of technology has made daily life more efficient and practical. Technology has begun to replace conventional parking methods that lack real-time information and are prone to human error. This study introduces a smart parking system innovation based on the ESP32 microcontroller as a solution to the limitations of conventional parking systems that are unable to provide accurate real-time information. The objective of this research is to design and test an ESP32based smart parking system capable of providing real-time and precise information on parking slot availability. The method employed is prototype engineering with a descriptive approach, which includes device design, component testing, and documentation. The test results show that the smart parking system works optimally and responsively. Infrared sensors are able to detect vehicles and activate servo motors that operate for 5 seconds. The LCD displays real-time parking information, while ultrasonic sensors provide accurate readings at distances of ≤15 cm. A red LED lights up as an indicator when a parking slot is occupied (distance <15 cm), while a green LED lights up when the slot is available (distance >15 cm). Integration with ThingSpeak and ThinkView applications runs smoothly with a fast update interval of approximately ±15 seconds, and the ESP32-CAM successfully records vehicles entering and exiting with clear results. Component power consumption is stable, with voltage and current measurements in line with their functions: the infrared sensor recorded an average voltage of 3.7 V without load and 0.15–0.16 V with load, with currents ranging from 3.7–4.1 mA without load to 7–9 mA with load. The SG90 servo motor maintained a stable voltage of around 4.9 V both with and without load, while current increased from 2.7–2.8 mA to 1213 mA during operation. In conclusion, the ESP32-based smart parking system has proven effective in providing real-time parking information, with recommendations for large-scale implementation and the addition of a license plate recognition feature to further enhance functionality.